IMPLEMENTASI KONSELING SUFISTIK DALAM MINIMALISASI PERILAKU NEGATIF SANTRI DI PONDOK PESANTREN NURUL FATA BONDOWOSO - Siti Mutmainnah; M.Syakur; Ach. Zukin (Fakultas Dakwah Universitas Ibrahimy, 2024)
Sufistic counseling is a process of assistance provided by the counselor to the counselee through the science of Sufism. Sufistic counseling is based on the basic values of Islamic teachings, namely the Koran and Hadith. The main goal that Sufism wants to realize is the presence of human beings. The aim of this research is to describe the implementation of Sufistic counseling in minimizing the negative behavior of students at the Nurul Fata Bondowoso Islamic Boarding School. This research uses a qualitative research method with a case study type of research. The results of research regarding the implementation of Sufistic counseling at the Nurul Fata Islamic Boarding School through three stages. First, the counselor invites students who behave deviantly to the counseling room. Second, providing assistance through Sufistic counseling using the tazkiyah annafs technique. Third, the counselee is treated with tahajud prayers, dhikr, bathing at night, and continues with reading the history of salafunas sholihin. So in this way the Sufistic counseling process not only minimizes negative dhahiriyah behavior but also spiritually.